Acquired Hemophilia A induced by Clopidogrel : A Case Report - Chofi Qolbi NA; Ibnu Purwanto; Vita Yanti Anggraeni (Smart Medical Journal, 2021)
ABSTRACT                                                   ABSTRACTIntroduction: Acquired hemophilia A (AHA) is a rare bleeding disorder caused by intervention of factor VIII by autoantibody. Most AHA cases arise from underlying medical conditions such as autoimmune disorders, cancers, drug/allergic reaction, with 50% cases are idiopathic.Case Presentation: 60-year old Asian male complained weakness worsened in the last two days accompanied by fatigue and pallor. Patients has history of percutaneous coronary intervention in proximal and distal of left anterior descending artery. Patient’s aPTT mixed with normal plasma before incubation is 41 seconds and after incubation became 59 seconds, it can be concluded that patient has time dependent FVIII antibody and his diagnosis became Acquired Hemophilia A. Methylprednisolone 0,5 mg/kg/day was added to his treatment following his diagnosisDiscussion and Conclusions : Drug induced AHA can be caused by several medications, including antibiotics (penicillin, sulfonamides, chloramphenicol), anticonvulsants (phenytoin), methyldopa, interferon-α, clopidogrel, fludarabine . In this case, patient has a history of percutaneus intervention with routine consumption of clopidogrel and aspirin for 3 months. Clopidogrel therapy for 3 months is suspected as a cause of AHA emergence in this patient. Short-term, high-dose immunosuppressive treatment with oral prednisone (1 mg/kg for 10 days, 0.5 mg/kg for 20 days, and 0.25 mg/kg for 15 days) can reduce the incidence of angiographic restenosis with minor secondary effects such as gastric pain, water and salt retention, and worsened hypertension in nearly 10% patients.Keywords: Acquired, Hemophilia, Clopidogrel, Coronary, Artery, Disesase ABSTRAKPendahuluan : Acquired hemophilia A (AHA) adalah kelainan perdarahan langka yang disebabkan oleh intervensi faktor VIII oleh autoantibodi. Sebagian besar kasus AHA timbul dari kondisi medis yang mendasari seperti gangguan autoimun, kanker, reaksi alergi / obat, dengan 50% kasus bersifat idiopatik.Persentasi Kasus : Laki-laki berusia 60 tahun mengeluh lemas memberat dalam dua hari terakhir disertai kelelahan dan pucat. Pasien memiliki riwayat percutaneuos coronary intervention di bagian proksimal dan distal arteri desenden anterior kiri. APTT pasien mixed dengan plasma normal sebelum inkubasi adalah 41 detik dan setelah inkubasi menjadi 59 detik, dapat disimpulkan bahwa pasien memiliki antibodi FVIII yang tergantung waktu dan diagnosisnya menjadi Acquired Hemophilia A. Methylprednisolone 0,5 mg / kg / hari ditambahkan pada pengobatan setelah diagnosis AHA tegak.Diskusi dan Kesimpulan : AHA yang diinduksi obat dapat disebabkan oleh beberapa obat, termasuk antibiotik (penisilin, sulfonamida, kloramfenikol), antikonvulsan (fenitoin), metildopa, interferon-α, clopidogrel, fludarabine. Dalam kasus ini, pasien memiliki riwayat percutaneous coronary intervention dengan konsumsi rutin clopidogrel dan aspirin selama 3 bulan. Terapi klopidogrel selama 3 bulan diduga sebagai penyebab munculnya AHA pada pasien tersebut. Pengobatan imunosupresif dosis tinggi jangka pendek dengan prednison oral (1 mg / kg selama 10 hari, 0,5 mg / kg selama 20 hari, dan 0,25 mg / kg selama 15 hari) dapat mengurangi kejadian restenosis angiografik dengan efek sekunder minor seperti sebagai nyeri lambung, retensi air dan garam, dan hipertensi yang memburuk pada hampir 10% pasien. Kata Kunci : Hemofilia yang di Dapat, Clopidogrel, Penyakit Jantung Koroner